Blockade of autophagy reduces pancreatic cancer stem cell activity and potentiates the tumoricidal effect of gemcitabine. Issue 1 (December 2015) - Yang, Ming-Chen; Wang, Hao-Chen; Hou, Ya-Chin; Tung, Hui-Ling; Chiu, Tai-Jan; Shan, Yan-Shen
Abstract Background Cancer stem cells (CSCs) are considered responsible for the recurrence and chemoresistance of cancer. Dysregulated autophagy is highly prevalent in many types of cancer including pancreatic cancer and has been implicated in cytoprotection and tumor promotion. This study aimed to investigate the role of autophagy in regulating cancer stemness and chemoresistance of pancreatic cancer. Methods The correlation between autophagy and CSCs and its clinical significance were analyzed using pancreatic cancer tissue microarrays. Genetic and pharmacological approaches were applied to explore the function of autophagy on CSC activity and gemcitabine resistance of pancreatic cancer cellsin vitro andin vivo . Results LC3 expression positively correlated with the expression of CSC markers aldehyde dehydrogenase 1 (ALDH1), CD44, and CD133 in pancreatic cancer tissues. High coexpression of LC3/ALDH1 was associated with both poor overall survival and progression-free survival. In pancreatic cancer cell lines, higher LC3-II expression was observed in the sphere-forming cells than in the bulk cells. Blockade of autophagy by silencingATG5, ATG7, andBECN1 or the administration of autophagy inhibitor chloroquine markedly reduced the CSC populations, ALDH1 activity, sphere formation, and resistance to gemcitabinein vitro andin vivo . Furthermore, osteopontin (OPN) was found to stimulate LC3-II, ALDH1, CD44, and CD133 expression in PANC-1 cells, whereas this effect could be prevented by OPN knockdown and autophagy blockade. After treatment with various inhibitors against the major signaling pathways downstream of OPN, only the inhibitor of NF-κB activation, BAY 1170–82, could effectively counteract OPN-induced autophagy and CSC activity. According to the histochemical results, pancreatic cancer patients manifesting high levels of OPN/LC3/ALDH1 and OPN/CD44/CD133 had poor survival. Conclusions Induction of autophagy mediated by OPN/NF-κB signaling is required for maintenance of pancreatic CSC activity. Combination of gemcitabine with pharmacological autophagy inhibitors is a promising therapeutic strategy for pancreatic cancer.